MI Double Feature: Multiple Imputation to Address Nonresponse and Rounding Errors in Income Questions - Joerg Drechsler; Hans Kiesl; Matthias Speidel (Austrian Journal of Statistics, 2015)
Obtaining reliable income information in surveys is difficult for two reasons. On the one hand, many survey respondents consider income to be sensitive information and thus are reluctant to answer questions regarding their income. If those survey participants that do not provide information on their income are systematically different from the respondents - and there is ample of research indicating that they are - results based only on the observed income values will be misleading. On the other hand, respondents tend to round their income. Especially this second source of error is usually ignored when analyzing the income information.